PENERAPAN PENDIDIKAN MATEMATIKA REALISTIK (PMR) DALAM MENINGKATKAN KEMAMPUAN MEMECAHKAN MASALAH MATEMATIKA SISWA SEKOLAH DASAR - Kurratul Aini (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2018)
This research aims to improve the ability to solve problems using fractions Realistic Mathematics Education (RME) students of class V SDN Sentol Laok. The subjects were students of class V SDN Sentol Laok many as 22 students. The experiment was conducted in three cycles., each cycle were two meetings that consist of planning, action, observation, and reflections. The data collection techniques used testing, observation, interviews, and documentations. This validity of data used triangulation techniques and triangulation of data sources. Data analysis applied the analysis of qualitative data and quantitative data. The results showed that the use of Realistic Mathematics Education (RME) can enhance problem solving abilities fractions fifth grade students of SDN Sentol Laok.